2009
DOI: 10.1038/emboj.2009.103
|View full text |Cite
|
Sign up to set email alerts
|

Novel crosstalk to BMP signalling: cGMP-dependent kinase I modulates BMP receptor and Smad activity

Abstract: Integration of multiple signals into the canonical BMP/Smad pathway poses a big challenge during the course of embryogenesis and tissue homeostasis. Here, we show that cyclic guanosine 3',5'-monophosphate (cGMP)-dependent kinase I (cGKI) modulates BMP receptors and Smads, providing a novel mechanism enhancing BMP signalling. cGKI, a key mediator of vasodilation and hypertension diseases, interacts with and phosphorylates the BMP type II receptor (BMPRII). In response to BMP-2, cGKI then dissociates from the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 68 publications
5
59
0
Order By: Relevance
“…The cyclic guanosine 3 0 ,5 0 -monophosphate-dependent kinase I (cGKI) associates with and phosphorylates the BMPRII cytoplasmic domain (Schwappacher et al 2009). On BMPRII activation by ligand binding, cGKI dissociates from the receptor and translocates to the nucleus bound to Smad1, assisting in transcriptional regulation by the Smad complex.…”
Section: Cytoplasmic Kinases: Cgkimentioning
confidence: 99%
“…The cyclic guanosine 3 0 ,5 0 -monophosphate-dependent kinase I (cGKI) associates with and phosphorylates the BMPRII cytoplasmic domain (Schwappacher et al 2009). On BMPRII activation by ligand binding, cGKI dissociates from the receptor and translocates to the nucleus bound to Smad1, assisting in transcriptional regulation by the Smad complex.…”
Section: Cytoplasmic Kinases: Cgkimentioning
confidence: 99%
“…It is widely used as an effective treatment for clinical PAH. 9 Recently, Schwappacher et al 10 reported that cGMP-dependent kinase I (cGKI) modulates BMP signaling in a mouse myoblast cell line. These authors found that cGKI interacts with BMPR-II, and that on BMP stimulation, cGKI is released to associate with activated Smad proteins and regulates gene expression as a nuclear cofactor for Smads.…”
mentioning
confidence: 99%
“…Like other BMP family members, BMP6 accessibility is modulated by specific antagonists. Receptor activation is controlled by co-receptors, by localization to distinct membrane microdomains, by endocytosis and by receptor associated proteins [38][39][40]. Approximately 40 TGF-β superfamily ligands differentially bind and signal through only 12 common receptors indicating that each receptor has multiple ligand-binding partners.…”
Section: Description Of Bone Morphogenetic Protein 6 (Bmp6)mentioning
confidence: 99%